2007
DOI: 10.1007/s11934-007-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of the complications of radical prostatectomy

Abstract: Over the past several years, the morbidity associated with radical prostatectomy has improved due to advances in surgical technique, better understanding of male pelvic anatomy, and improved perioperative care. Despite these advances, patients are still at risk for several complications both intraoperatively and in the postoperative course. These risks include significant blood loss, rectal injury, ureteral injury, thromboembolic events, urinary incontinence, impotence, and a perioperative death rate of less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
7
0
2
Order By: Relevance
“…Considering the adverse effects associated with radical therapy (22), and that most men affected with prostate cancer will die with—rather than from—this disease (23), there is an urgent need for improved tools to distinguish lethal from indolent disease at diagnosis. Identification of genetic markers associated with lethal prostate cancer hold promise to advance the understanding of the biological aspects behind the metastatic potential of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the adverse effects associated with radical therapy (22), and that most men affected with prostate cancer will die with—rather than from—this disease (23), there is an urgent need for improved tools to distinguish lethal from indolent disease at diagnosis. Identification of genetic markers associated with lethal prostate cancer hold promise to advance the understanding of the biological aspects behind the metastatic potential of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal injury during RP has been reported in 0.3% to 3.8% of cases. 10,22 During RRP and RPP, most rectal injuries occur while transecting the rectourethralis muscle. 23,24 In a series of 1,000 LRP, Guillonneau et al reported 13 rectal injuries, 10 of which occurred during dissection of the posterior surface of the prostate at the apex.…”
Section: Rectal Injurymentioning
confidence: 99%
“…A better understanding of pelvic anatomy, including the vasculature and innervation surrounding the prostate, has led to a significant decrease in the mortality and relative morbidity for patients undergoing RP. 10,11 Furthermore, improved surgical training and the establishment of centers specializing in minimally invasive surgery have increased the popularity of laparoscopic (or robotic-assisted laparoscopic) radical prostatectomy (LRP) for the treatment of localized prostate cancer. Minimally invasive techniques such as LRP have also led to a decreased length of stay, shorter convalescence, and improved cosmesis.…”
mentioning
confidence: 99%
“…[3] Importantly, there has been a decrease in the rate of rectal injury during radical prostatectomy operations in recent years, which may be due to the more refined surgical techniques and increasing anatomical knowledge of the male pelvis. [4] Previous studies have suggested that the rates of rectal injury are higher when the surgeon is unfamiliar with radical prostatectomy. Indeed, Heinzer et al [5] reported a rectal injury rate of 2% among patients who were operated upon later in the study compared with 7.8% in the group of patients who were operated upon at the beginning of the study.…”
Section: Discussionmentioning
confidence: 99%